THE EFFECT OF ENVIRONMENT CONTROL, RISK ASSESSMENT AND MONITORING ON THE PREVENTION OF FRAUD (A SURVEY AT DINAS PENDIDIKAN ACEH PROVINCE) - Muyassir Kahar; M. Rizal Yahya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this research is to examine the effect of environment control, risk assessment, and monitoring on the prevention of fraud at Dinas Pendidikan Aceh Province. The population of this research is all employees at Dinas Pendidikan Aceh Province which totaling 337 employees ( respondents). The sample method that will be used for this study is simple random sampling. Data collection techniques were conducted with questionnaires. The results of this research shown that simultaneously and partially, the environment control, risk assessment, and monitoring affected on the prevention of fraud at Dinas Pendidikan Aceh Province.